2022
DOI: 10.12912/27197050/147154
|View full text |Cite
|
Sign up to set email alerts
|

Technologies for Environmental Safety Application of Digestate as Biofertilizer

Abstract: The purpose of the paper is to determine the environmentally safe and economically feasible technology of biofertilizer production from the digestate including dewatering process. Methodological basis is based on the systematic approach to the determination of factors effected on the distribution of nutrients and pollutants between liquid and solid fractions after digestate separation. We studied modern technologies aimed at dewatering the digestate and reduction of its volume, showed their effectiveness. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The radiation background of the experimental site was 10.5 µR/h, the soil at the research site was 11.0-12.0 µR/h, and the phosphogypsum itself was 12.5 µR/h. Summarising a series of ecological regularities of the impact of phosphogypsum on the soil complex, confirmed by previous studies in Ukraine [78,79], and consistent with results obtained by other researchers in this field [80][81][82], we can use the phosphogypsum to improve ecosystem services.…”
Section: Discussionsupporting
confidence: 90%
“…The radiation background of the experimental site was 10.5 µR/h, the soil at the research site was 11.0-12.0 µR/h, and the phosphogypsum itself was 12.5 µR/h. Summarising a series of ecological regularities of the impact of phosphogypsum on the soil complex, confirmed by previous studies in Ukraine [78,79], and consistent with results obtained by other researchers in this field [80][81][82], we can use the phosphogypsum to improve ecosystem services.…”
Section: Discussionsupporting
confidence: 90%
“…Our previous research study showed that centrifugation is one of the most effective solid-liquid separation technologies for digestate to obtain a solid fraction with a high level of dry matter and improve nutrient fractionation between the two fractions [16]. Thus, given the uneven distribution of nutrients in solid and liquid fractions (Figure 3), solid-liquid separation gives the two products with specific functionality [4].…”
Section: Resultsmentioning
confidence: 99%
“…All these factors are considered promising for using organic-mineral complexes of biofertilizers. Mineral component improves both the elemental composition of the biofertilizer and acts as an additional element of nutrition in the processes of bacterial processing of organic raw materials, with an impact on the quality of the product [15].…”
Section: Literature Reviewmentioning
confidence: 99%